ON SOME SEQUENCE SPACES OF NON-ABSOLUTE TYPE - Ercan, Sinan; Bektas, Cigdem A. (Univ Kragujevac, Fac Science, 2014)
In this paper, we introduce the notion of lambda(v)-convergent and bounded sequences. Further, we introduce the spaces l(infinity)(lambda) (Delta(v)), c(0)(lambda) (Delta(v)) and c(lambda) (Delta(v)), which are BK-spaces of non-absolute type and we prove that these spaces are linearly isomorphic to the spaces l(infinity,) c(0) and c, respectively. Moreover, we establish some inclusion relations between these spaces.
Keywords: Sequence spaces of non-absolute type; BK-spaces; Difference Sequence Spaces